M8 Cost variations of asthma over 10 years in adults. (December 2018) - Portas, L; Calciano, L; Corsico, AG; Cazzoletti, L; Cerveri, I; Gerbase, MW; Gislason, D; Gronseth, R; Heinrich, J; Jögi, R; Johannessen, A; Marcon, A; et al.
Abstract : We investigated the 10 year variation of asthma cost by the change of disease severity/control in adults from 11 European countries taking part in a cohort study (the European Community Respiratory Health Survey – ECRHS). We identified 562 adults (aged 29–56) with physician-diagnosed current asthma at the ECRHS II (1999–2003, baseline) and ECRHS III (2010–2013). At each survey, they were classified as 'intermittent' or 'persistent' (GINA 2002) with persistent asthmatics further classified as 'controlled/partly controlled' (CP) or 'uncontrolled' (U) (GINA 2016). Change in disease status was considered 'worsened' (from intermittent to persistent, from CP to U or U at both the occasions; n=146), 'improved' (from persistent to intermittent, from U to CP or CP at both the occasions; n=136) or 'unchanged' (intermittent at the ECRHS II and ECRHS III; n=128). The annual cost per patient was computed from the societal perspective following the bottom-up approach, using rates/wages/prices obtained at national level in 2004 (ECRHS II; converted to a 2013 equivalent) and 2013 (ECRHS III). The variation of the annual cost per patient was estimated by the change in disease status using a 2-level random-intercept Laplace quantile regression model, adjusting for sex, age, ever smoking, low socio-economic status (centre: level 2 unit). At baseline, the mean annual cost was 193€, 790€ and 3, 120€ per patient with intermittent, CP persistent or U persistent asthma, respectively. Compared to patients whose disease status was unchanged, those with an improved or worsened asthma showed reduced [−145 (95% CI: −275, –15) €; p=0.029] and increased [185 (95%CI: 59, 311) €; p=0.005] annual costs, respectively. Our study suggests substantial cost savings if asthma severity/control improved among adult patients in Europe.